Evaluation of the Body Burden of Short- and Medium-Chain Chlorinated Paraffins in the Blood Serum of Residents of the Czech Republic - Denisa Parizkova; Aneta Sykorova; Jakub Tomasko; Ondrej Parizek; Jana Pulkrabova (Journal of Xenobiotics)
Short- and medium-chain chlorinated paraffins (SCCPs and MCCPs) are environmental contaminants known for their persistence and bioaccumulation in fatty tissues. SCCPs are considered potential carcinogens and endocrine disruptors, with similar effects expected for MCCPs. This study investigated the body burden of SCCPs and MCCPs in residents of two regions of the Czech Republic with different levels of industrial pollution. Blood serum samples from 62 individuals in Ceske Budejovice (control area) and Ostrava (industrial area) were analysed. The results showed higher concentrations of SCCPs (<120–650 ng/g lipid weight (lw)) and MCCPs (<240–1530 ng/g lw) in Ostrava compared to Ceske Budejovice (SCCPs: <120–210 ng/g lw, MCCPs: <240–340 ng/g lw). The statistical analysis revealed no significant correlations between chemical concentrations and demographic variables such as age, BMI, or gender. The findings are consistent with European and Australian studies but significantly lower than levels reported in China. This is the first comprehensive survey of SCCPs and MCCPs in human blood serum in the Czech Republic and the second study in Europe. The data collected in this study are essential for assessing SCCPs and MCCPs. They will contribute to a better understanding the potential health risks associated with exposure to these chemicals.